Effects of Lorentz violation in the Bose-Einstein condensation. (29th December 2020) - Furtado, J.; Ramos, A. C. A.; Assunção, J. F.
Abstract: In this paper we study the corrections emergent from a Lorentz-violating CPT-odd extension of the complex scalar sector to the Bose-Einstein condensation and to the thermodynamics parameters. We initially discuss some features of the model to only then compute the corrections to the Bose-Einstein condensation. The calculations are done by computing the generating functional, from which we extract the thermodynamics parameters. We also obtain a Lorentz-violating correction for the critical temperature T c that sets the Bose-Einstein condensation.